Communication skills : the easy way to enhance your interpersonal skills. (Rugeley : Focus Multimedia Limited, 2005)
Bolster your communication skills and confidence with this invaluable guide.
Ελάχιστες απαιτήσεις συστήματος: Windows® 98/Me/NT/2000/XP; Pentium® I33or equivalent; 80MB hard drive; 32MB memory; 800x600x16bit colour.
Keywords: CD-ROMs.; Interpersonal communication -- CD-ROMs.